THE EFFECT OF GARLIC STEPPING ON BLOOD PRESSURE IN ELDERLY WOMEN WITH HYPERTENSION IN THE JATI CITY HEALTH CENTER WORK AREA PROBOLINGGO IN 2022 - Wahyuningtyas, Silvyana; Endah Sary, Yessy Nur; Rohmatin, Homsiatur (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
High blood pressure or hypertension (Hypertension) is a condition which a person experiences an increase in blood pressure above normal as indicated by the Systolic (top) and diastolic (bottom number) and blood pressure checks using a blood pressure measuring device in the form of a mercury cuff ( sphygmomanometer). The purpose of this study was to analyze the effect of giving steeped garlic on blood pressure in elderly women with hypertension in the Jati City Health Center Work Area Probolinggo In 2022. The design of this study was a pre Experiment with a One Group Pretest Posttest Design approach. The total population in this study were 80 elderly women with hypertension and the number of samples was 15 respondents. The instruments used in this study were blood pressure meter, sphygmomanometer and observation sheet, the results then analyzed using the Wilcoxon test. The results of the study before giving the consumption of steeped garlic most (60%) of respondents experienced a mild blood pressure, and after consuming the steeped garlic half (53.3%) had normal blood pressure. Based on the Wilcoxon statistical tests, it is known that the significance value is 0.001 with α 0.05. Because the significance value <α ,then H0 is rejected and H1 is accepted, which means that there is the effect of giving steeped garlic on blood pressure in elderly women with hypertension. It is hoped that the results of this study can be used as input for the elderly with hypertension by using non-pharmacological treatment, namely the provision of steeping garlic in addition to the low price, the materials used are also easily obtained.